2020
DOI: 10.1002/lary.28650
|View full text |Cite
|
Sign up to set email alerts
|

The Shape of Things to Come: In‐Hospital Three‐Dimensional Printing for Mandibular Reconstruction Using Fibula Free Flap

Abstract: Objectives/Hypothesis: The aim of this study was to explore whether the production of in-hospital, low-cost surgical cutting guides would be possible and to assess different cutting guide shapes to facilitate the surgery and the application with instruments. Study Design: Cohort study. Methods: Using free computer-aided design software, surgical cutting guides for the mandible and fibula were designed and used to perform virtual segmental osteotomies and fibula transplants in seven patients. Results: Fourteen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Among the most common were the cost and duration of patient-specific device production, especially when outsourced to specialized commercial entities. 23,28,29,39,49,62,63,72,76 The price of 3D-printed implants is estimated to be 2-to 5-times higher compared to conventional implants, 28,128,129 and additional costs include preoperative virtual planning, device design, and the production of trials or implant variations. Outsourcing is virtually inevitable for titanium implants due to their complex structure and the high cost of EBM machines.…”
Section: Advantages and Drawbacks Of The Use Of 3d Printing For Medic...mentioning
confidence: 99%
See 2 more Smart Citations
“…Among the most common were the cost and duration of patient-specific device production, especially when outsourced to specialized commercial entities. 23,28,29,39,49,62,63,72,76 The price of 3D-printed implants is estimated to be 2-to 5-times higher compared to conventional implants, 28,128,129 and additional costs include preoperative virtual planning, device design, and the production of trials or implant variations. Outsourcing is virtually inevitable for titanium implants due to their complex structure and the high cost of EBM machines.…”
Section: Advantages and Drawbacks Of The Use Of 3d Printing For Medic...mentioning
confidence: 99%
“…Outsourcing is virtually inevitable for titanium implants due to their complex structure and the high cost of EBM machines. However, studies involving relatively simple devices printed in polymer-based materials also reported notably lower cost compared to conventional devices, 76,104 and successful in-house design and fabrication by medical staff. 23,76,110 Longer waiting periods for custom implantable devices may predispose patients to malignant changes, disease progression or anatomical alterations, which can complicate implantation.…”
Section: Advantages and Drawbacks Of The Use Of 3d Printing For Medic...mentioning
confidence: 99%
See 1 more Smart Citation
“…Today, however, an in‐house and self‐developed manufacturing approach for mandibular cutting guides has been developed (Bosc et al, 2017; Ganry et al, 2017). This new approach is proved to be reliable and helpful tool in reconstructive surgery (Li et al, 2018; Zavattero et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In 79 cases, only type 1 models were printed; in 68 cases, type 1 models were printed together with type 2 and 3 models. 2 …”
mentioning
confidence: 99%